Estimasi Biaya Pemeliharaan Bangunan Berdasarkan Pedoman Pemeliharaan Dan Perawatan Bangunan Gedung (Permen Nomor : 24/PRT/M/2008) (Studi Kasus Bangunan Masjid Islamic Center Bangkinang) - Adriansyah Adriansyah; Rian Trikomara (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Building maintenance consistently has become a requirement that must be fulfilled, particularly for buildings that functioned in the public interest including the Islamic Centre Mosque Bangkinang . Maintenancing and monitoring continuously of the condition of the building components will greatly help to reduce the large financing and can reduce the rate of severe damage . Building maintenance requires a proper maintenance manual in accordance with existing regulations (No : 24/prt/m/2008 ) which can then provide an overview of the estimated costs necessary in the maintenance of the building . Based on the analysis using the methods in approximate estimate , the percentage obtained 1.69%. While the cost of necessary repairs is Rp.337.507.095 , 29 . But in overall, the condition of the building Masjid Islamic Centre Bangkinang is still categorized in slightly damaged. As for the cost of maintenance per-year amounted to Rp884, 691,280.45 which is predicted to be increased every year.  Keywords : repair costs , maintenance costs , estimated price forecasts ( approximate  estimate) , the extent of damage.